Webinar On Business Sustainability During The Covid-19 Pandemic For University Students and Public - Suwinto Johan; Sarah Novalina Sipayung; Chesy Conysia Fitri Safa'at; Muslih Abdillah (Universitas Andi Djemma, 2022)
The pandemic has posed many challenges for companies to survive. As a result, many layoffs of workers. Layoffs and company bankruptcies have been common during the pandemic. Many businesses face business sustainability. The main objective of this activity is to provide knowledge about the issues of international business sustainability facing every part of the world today, namely about the impact of Covid-19 and its impact on business. This activity focuses on one of the industries most affected, namely aviation. Flights were directly impacted by Covid-19 starting in early 2020 when many airlines had their flights suspended due to social restrictions and quarantine policies, making it difficult for airlines to maintain cash flow with the decline in the number of flights both domestically and internationally. One of the cases where international companies need to maintain the sustainability of their business. In this activity, international business continuity management students will gain knowledge about how airlines are impacted by Covid-19, and how they deal with these issues to sustain the business themselves. This training method is in the form of a webinar method, where speakers share experiences.